Effectiveness of chemotherapy in advanced differentiated thyroid cancer: a systematic review. Issue 2 (February 2016) - Albero, Ana; Lopéz, Juliana Ester; Torres, Alberto; de la Cruz, Luis; Martín, Tomas
Abstract : In differentiated thyroid carcinoma refractory to radioactive iodine (CDT-RTI), chemotherapy has been considered for decades to be the only systemic therapy with palliative purpose. Phase II studies assessing the efficacy of different chemotherapy outlines have been published. Nevertheless, phase III studies in these tumours have not been performed. Our objective is to evaluate the effectiveness of chemotherapy in patients with CDT-RTI by a systematic review of published studies. Systematic research of the literature in Medline and Embase databases (among others) was carried out. The full texts of selected references were analysed by two independent reviewers and then assessed for risk of bias in each study. We also extracted data using specifically designed questionnaires. Later, a qualitative synthesis of results was performed and pooled data were calculated. We found that 16 studies with 473 patients published in the last 40 years were included out of 509 identified references in databases. Thirteen studies (176 patients) included data on response to treatment and histology. Four studies included 70 patients only with well-differentiated non-medullary tumours. Response rate (RR) was 22.1% (0–57%) for 13 studies, 25% for the 176 patients and 27.1% for the 70 patients, with 2.5, 3.4 and 2.8% complete responses respectively. Survival times could not be assessed or pooled due to the lack of data and heterogeneity of the studies, and was determined to have a high risk of bias. Although it has not been possible to find solid evidence about the efficacy of chemotherapy, the results shown indicate that it may have some effectiveness, although this should be proven with well-designed studies using modern drugs.